Perceptions of nurses and parents about caring behavior in children with COVID-19: A mix method study - Yunita Ida R Sipahutar; Heni Suzana Mediani; Fauziah Rudhiati; Yayat Suryati; Nunung Nurjanah; Le Thi Thanh Tuyen (Journal of Holistic Nursing Science, 2022)
The prevalence of children experiencing COVID-19 infection is increased worldwide. This situation alarmed pediatric nurses to work more closely with the group of patients. Moreover, children’s parents also suffered health issues due to the pandemic. Understanding of implementation theory of Human Caring will help the nurses cope with the problem. Therefore, the objective of the study is to identify the perception between nurses and parents about nurses' caring behavior in hospitals. The study used a mixed method design integrating purposive sampling techniques. The instrument was the CNPI-70 consists of 70 items and 10 carative factors/subscales based on Watson's Theory of Caring. The study documented that the nurse’s perception is lower than the parent’s perception. It is important to increase the knowledge related to the perception through health education, routine training along with intensive discussion in Hospital. Keywords: COVID-19 infection; nurse’s perception; parent’s perception; theory of human caring; pediatric nurses